From colony to first patch: Processes of prey searching and social information in Cape Gannets. (13th August 2014) - Thiebault, Andréa; Mullers, Ralf; Pistorius, Pierre; Meza-Torres, María Andrea; Dubroca, Laurent; Green, David; Tremblay, Yann
Abstract: Seabirds forage in a highly dynamic environment and prey on fish schools that are patchily distributed. Colonially breeding seabirds regularly commute back and forth from their colony to foraging areas and need to acquire information on the location of food before and/or during each foraging trip. The use of conspecifics as cues to locate prey has long been debated, and although the hypothesis was backed up by modeling studies, observations have been contradictory. We deployed GPS devices coupled with micro video cameras on Cape Gannets to observe the social context of foraging seabirds and the influence of conspecifics on the movement of individuals. The Cape Gannets reached their first patch using a succession of flights interrupted by stops on the water, during which the birds were mainly preening. During flight, the birds reacted to conspecifics by changing direction, either flying in the opposite direction of conspecifics that were flying toward the colony or following conspecifics outward. The time to reach the first patch was significantly reduced (by half) when the birds reacted to conspecifics in these different ways, compared with the birds that did not react. The use of conspecifics flying toward the colony to find food is consistent with the hypothesis that colonies can act as a focal place for information transfer, with foragers updating their flying direction when they detect conspecifics flying toward the colony. The fine-scale reaction of seabirds toward each other at sea, and the associated improved foraging efficiency, as well as the division of trips into a succession of flights, constitute elements that indicate the existence and the use of a structured network among foraging Cape Gannets.